Electrochemical and diffuse reflectance study on tetrahedral ε-Keggin-based metal–organic frameworks. Issue 50 (20th June 2017) - Nie, Zhong-Bin; Zhang, Min; Su, Tan; Zhao, Liang; Wang, Yuan-Yuan; Sun, Guang-Yan; Su, Zhong-Min
Abstract : Two polymolybdate-based metal–organic frameworks composed of Zn-ε-Keggin nodes and semi-rigid organic linkers were successfully synthesized. The electrochemical behaviors of these two compounds were studied, as well as their diffuse reflectance performance. Abstract : Herein, two new polyoxometalate-based metal–organic frameworks consisting of Zn-ε-Keggin nodes and semi-rigid organic linkers, [TBA]3 [PMo8 V Mo4 VI O36 (OH)4 Zn4 ][CPBPC]2 (1 ) and [TBA]3 [PMo8 V Mo4 VI O37 (OH)3 Zn4 ][PTABAB][HPTABAB]·7H2 O (2 ) (where CPBPC = 4′-(4-carboxylatophenoxy)-[1, 1′-biphenyl]-4-carboxylate and PTABAB = 4, 4′-((6-(phenylamino)-1, 3, 5-triazine-2, 4-diyl)bis(azanediyl))dibenzoate), were successfully synthesized. In1, Zn-ε-Keggin units were bridged by CPBPC fragments to form an eight-fold interpenetrating framework with diamond topology. In2, the adjacent 2D layers are constructed from Zn-ε-Keggin units and PTABAB moieties interlocked with each other to generate a double layer, which was further packed in an AAA sequence. The electrochemical behaviours of these two compounds were studied, and they exhibit good electrocatalytic activities towards the reduction of nitrite ions. Moreover, their diffuse reflectance was also investigated to obtain their bandgaps of around 1.1 eV, suggesting that they are potential and promising semiconductor materials.